2012
DOI: 10.1037/a0026896
|View full text |Cite
|
Sign up to set email alerts
|

Mutational ataxia resulting from abnormal vestibular acquisition and processing is partially compensated for.

Abstract: Due to the multisensory input into the balance system, the loss of one input, such as an ear, can generally be compensated for. However, when a mismatch or incomplete loss of inputs occurs, the ability to compensate for the stimulus misrepresentation may be compromised. The inner ear and cerebellum are important input and processing centers for balance but no genetic models have been generated to assess balance or compensation in the abnormal development of both these organs/brain areas. Important to their for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 63 publications
7
30
0
Order By: Relevance
“…While there was substantial lengthening of the organ of Corti from P0 to P21 for both WTs (3.36+/−0.094mm vs. 4.71+/−0.27mm; p<0.001) and dCKOs (3.40+/−0.13mm vs. 4.79+/−0.27mm; p<0.001), there was no significant change between P21 and four months of age for WTs (4.71+/−0.27mm vs. 4.78+/−0.062mm; p=0.558) and dCKOs (4.79+/−0.27mm vs. 4.76+/−0.17mm; p=0.779) (Figure 2G). These WT length measurements were consistent with previously published data (Kopecky et al, 2011; Kopecky et al, 2012a; Pan et al, 2011). Furthermore, equivalence testing confirmed that P0 WT and P0 dCKO mice (df=26) were identical and P21 WT and P21 dCKO mice (df=26) as well as four month WT and four month dCKO mice (df=26) were the same (Figure 3A).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…While there was substantial lengthening of the organ of Corti from P0 to P21 for both WTs (3.36+/−0.094mm vs. 4.71+/−0.27mm; p<0.001) and dCKOs (3.40+/−0.13mm vs. 4.79+/−0.27mm; p<0.001), there was no significant change between P21 and four months of age for WTs (4.71+/−0.27mm vs. 4.78+/−0.062mm; p=0.558) and dCKOs (4.79+/−0.27mm vs. 4.76+/−0.17mm; p=0.779) (Figure 2G). These WT length measurements were consistent with previously published data (Kopecky et al, 2011; Kopecky et al, 2012a; Pan et al, 2011). Furthermore, equivalence testing confirmed that P0 WT and P0 dCKO mice (df=26) were identical and P21 WT and P21 dCKO mice (df=26) as well as four month WT and four month dCKO mice (df=26) were the same (Figure 3A).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, equivalence testing confirmed that P0 WT and P0 dCKO mice (df=26) were identical and P21 WT and P21 dCKO mice (df=26) as well as four month WT and four month dCKO mice (df=26) were the same (Figure 3A). Our data suggest that the loss of both N-Myc and L-Myc in differentiated hair cells had no effect on the length of the organ of Corti (Figure 2) or its overall development (Figure 1); this contrasted with the disorganization and loss of hair cells as well as the reduction in length of the organ of Corti in the Pax2-Cre N-Myc CKO mice at P21 as previously reported (Dominguez-Frutos et al, 2011; Kopecky et al, 2011; Kopecky et al, 2012a). Figs 2 and 3…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Catwalk assay was performed for gait analysis using Noldus system (Wageningen, Netherlands) as previously reported (Kopecky, Decook et al 2012). Mice were placed at the end of a corridor and allowed to move freely.…”
Section: Methodsmentioning
confidence: 99%
“…The automated CatWalk gait analysis method is also applied in models involving other types of pain and peripheral nerve damage and movement disorders like Parkinson's disease [21][22][23]. Abnormal gait was described in mice exhibiting (cerebellar) ataxia, by using paw print area, contact area, base of support of the hindpaws, stand, swing and step regularity [24][25][26]. The aim of this study was to identify gait changes in the Ndufs4 −/− mouse by using the CatWalk system.…”
Section: Introductionmentioning
confidence: 99%